Desirable Futures: Write Me a Letter - Gergan, Mabel; Gupta, Pallavi; Lookabaugh, Lara; McMillan, Caitilin; Smith, Sara; Vasudevan, Pavithra (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
In this special issue, we propose the letter as a form with geographic potential. Building on prior work on letters in geography, Black feminism, and Indigenous studies, we draw on a collection of sixteen letters in the section to build a case for letters as time travel, anticolonial epistemology, feminist geographic method, and worldmaking praxis. We bring together letter writers who speak to their ancestors known and unknown, to future generations, to ideas, to activists, to places, and to strangers—and weave them into a messy and generative conversation on the kinds of spaces that letters make between and among us. Our intention is to build on recent work in geography to experiment with what the letter makes possible for us as geographers.